Moral Sensitivity, Ethical Experiences, and Promotion of the Civility of Staff Nurses: A Review - Hameeda M. Aljanabi; Robin Maarman; Masoma A. Kehlini; Ola Mousa (Recent Trends in Arts and Social Studies Vol. 1, 2023)
The nursing construct is an extensive idea and an ethical responsibility to uphold and protect a patient’s integrity and dignity. Healthcare is, however, quickly changing as a result of technological advancements and medical advancements. Nurses play a significant role in health care research, support of patients, management, policy writing, and decision making. Working under time constraints and with a lot of responsibility causes nurse burnout and ethical violation, which limits their ability to behave morally and ethically in situations requiring effective patient care. For "carrying out nursing responsibilities with an attitude coherent with quality in care for patients and the ethical standards of the profession," refer to the nursing code of ethics. The review argument that follows discusses moral sensitivity, ethical experiences, and the promotion of staff nurses’ civility. The paper presents an overview of other research studies on this topic. Both historic and contemporary authors argue for a variety of ethical experiences, such as privacy and data protection as well as nurses’ capacity for moral judgment.